Respostas

2014-02-25T19:09:46-03:00
x² + 3-2x=0 3 =  { - 1,3 }
1 2 1
2014-02-25T21:20:16-03:00
x²  +  3 _ 2x =  0
3

-___x²______  +    __9_______      _    ___6x____ -= 0  
     3                        3                          3


  x²  + 9  - 6x = 0                            + 6 +√0              
                                                                     
   - b + √Δ                                              2
                                                        6+0
         2a                                                    = 3       
                                                           2

Δ= 6²  -  4 x 1 x 9                        6-0
Δ = 36 - 36                                         =3            RESPOSTA: 3,3
Δ = 0                                            3
1 4 1